2015
DOI: 10.1093/nar/gku1395
|View full text |Cite
|
Sign up to set email alerts
|

A systematic survey of the Cys2His2 zinc finger DNA-binding landscape

Abstract: Cys2His2 zinc fingers (C2H2-ZFs) comprise the largest class of metazoan DNA-binding domains. Despite this domain's well-defined DNA-recognition interface, and its successful use in the design of chimeric proteins capable of targeting genomic regions of interest, much remains unknown about its DNA-binding landscape. To help bridge this gap in fundamental knowledge and to provide a resource for design-oriented applications, we screened large synthetic protein libraries to select binding C2H2-ZF domains for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 71 publications
4
112
0
1
Order By: Relevance
“…For example, large-scale B1H assays and structural analyses have shown that in C2H2-zf proteins, residues at the finger–finger interface and the order of fingers within an array frequently influence specificity [48,49]. In particular, adjacent fingers can constrain mutual finger orientation and influence the positioning of specificity-determining residues [46,50].…”
Section: Complexities Of Tf Binding Determinantsmentioning
confidence: 99%
“…For example, large-scale B1H assays and structural analyses have shown that in C2H2-zf proteins, residues at the finger–finger interface and the order of fingers within an array frequently influence specificity [48,49]. In particular, adjacent fingers can constrain mutual finger orientation and influence the positioning of specificity-determining residues [46,50].…”
Section: Complexities Of Tf Binding Determinantsmentioning
confidence: 99%
“…By homology modeling, we illustrated a possible alteration in function caused by missense variants. ZBTB18 encodes for a protein with four C2H2 Zinc fingers, structures found in nearly half of DNA‐binding factors and known to be involved in numerous biological processes (Persikov et al., ). Our homology model shows how the recurrent p.Arg464His substituting variant in the C2H2 structure of ZNF 3 probably affects DNA‐binding properties.…”
Section: Discussionmentioning
confidence: 99%
“…However, other results suggest widespread genomic interactions with these proteins that can lead to off-target transcriptional dysregulation (Falahi et al 2013;Grimmer et al 2014). Surveys of ZF nuclease specificities demonstrate that off-target effects can be prevalent (Cornu et al 2008;Pattanayak et al 2011), although this off-target activity may be mitigated by optimized design tools that minimize confounding factors such as context-dependent ZF domain effects (Isalan et al 2001;Maeder et al 2008;Sander et al 2011;Gupta et al 2012;Persikov et al 2015).…”
Section: Specificity Of Zfs Tales and Crispr/cas9 Systemsmentioning
confidence: 99%